Wenlin Wang: a “weird doctor” in defiance of the Matthew effect - Jiang, Reeyan; Liao, Lili (Journal of Thoracic Disease, 2019)
There is a concept in economics called “the Matthew effect”, which describes a phenomenon in which a person with more resources is more likely to be more successful. This opinion has led to familiar assertions like “poor families make poor children”, and “your platform is more important than your personal ability”. However, is it possible that every life is planned according to economic principles?